O avesso do Ego no existencialismo de Sartre - Violante, Tiago Monteiro (2011)
One of the constants of Sartre's theoretical concerns is the question of the constitution of the ego. It can be seen a detailed siege by the French philosopher, in search of this existential problem par excellence: the relationship of consciousness to self. The ego is a structure of consciousness immanent constitute or is a product of a transcendent poetic creation held by such transcendental field? What this paper intends to present is how Sartre captures the features, functions and meanings that the ego is in his existentialism. It is necessary, however, cut this issue on the horizon of an argumentative progression on the foundations of human reality, presented since his first work, The Transcendence of the Ego, to his most important and significant, Being and Nothingness.